A case-control study of bladder cancer in the United States rubber and tyre industry. Issue 3 (August 1981) - Checkoway, H; Smith, A H; McMichael, A J; Jones, F S; Monson, R R; Tyroler, H A
Abstract : A case-control study of bladder cancer was conducted in five United States rubber and tyre companies to determine if there were high-risk jobs and work areas within the industry. The study included 220 male cases of bladder cancer, of whom 107 were identified from hospital record reviews and 113 from death certificates. Each case was matched individually with two industry controls by sex, race, year of birth, and company. One control was matched additionally by year of hire and duration of employment. Comparisons of cases and controls not matched by year of hire and age of hire showed no differences for those variables, which suggests that age and calendar period of first exposure to the industry were not risk determinants. When the work histories of both cases and controls were contrasted it was found that cases were more likely than controls to have worked in milling (odds ratio (OR) = 1.91) and calender operation (OR = 2.21) jobs. The relative risk estimates for milling and calender operation both exhibited linear trends of increase with duration of exposure. Milling and calender operation jobs entail potential exposures to volatilised reaction products from heated rubber stock. A better understanding of aetiological associations with job type will require more detailed characterisation of the work environment with regard to the sources and levels of aromatic amines and other suspected bladder carcinogens.